2014
DOI: 10.3109/19396368.2014.948102
|View full text |Cite
|
Sign up to set email alerts
|

Is sperm hyaluronic acid binding ability predictive for clinical success of intracytoplasmic sperm injection: PICSI vs. ICSI?

Abstract: Although intracytoplasmic sperm injection (ICSI) is now a widely-used technique, it is still of interest to improve our knowledge as to which is the best spermatozoon to be selected for ICSI. Infertile men have increased risks of producing aneuploid spermatozoa. Using hyaluronic acid (HA)-binding sperm selection may reduce the genetic risks such as chromosomal aberrations of offspring. In the present study we examined the clinical success of ICSI with HA-selected sperm ('physiologic' ICSI, PICSI) compared to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
55
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 39 publications
7
55
3
Order By: Relevance
“…The chemical modification of glass with HA was confirmed by fluorescence imaging of Fluorescein isothiocyanate (FITC) labeled HA and by observing the change of hydrophobicity of glass ( Figure S1, Supporting Information). [28][29][30] Unlike the physical absorption of HA hydrogel on a plastic substrate in PICSI dishes, [31] we functionalized the glass surface with HA using permanent chemical bonding. After sperm settled down on the HA glass, mature and live sperm were bound to HA by the CD44 cell receptor, [24][25][26][27] while nonmotile sperm simply settled on the HA glass.…”
Section: Preparation Of Sperm For Morphology and Dna Integrity Analysismentioning
confidence: 99%
“…The chemical modification of glass with HA was confirmed by fluorescence imaging of Fluorescein isothiocyanate (FITC) labeled HA and by observing the change of hydrophobicity of glass ( Figure S1, Supporting Information). [28][29][30] Unlike the physical absorption of HA hydrogel on a plastic substrate in PICSI dishes, [31] we functionalized the glass surface with HA using permanent chemical bonding. After sperm settled down on the HA glass, mature and live sperm were bound to HA by the CD44 cell receptor, [24][25][26][27] while nonmotile sperm simply settled on the HA glass.…”
Section: Preparation Of Sperm For Morphology and Dna Integrity Analysismentioning
confidence: 99%
“…Eight publications were excluded as no full text article was published (Barak et al, 1999;Kim et al, 2014;Menezo et al, 2010;Sanchez et al, 2005;Saymé et al, 2013;Worrilow et al, 2005Worrilow et al, , 2006Worrilow et al, , 2007. Two studies were excluded because the raw data were not presented (Mokánszki et al, 2014;Nasr-Esfahani et al, 2008). An attempt was made to contact investigators via email to obtain missing information but no replies were received.…”
Section: Systematic Search Selection and Data Extractionmentioning
confidence: 99%
“…A potential link between hyaluronic-acid-binding (which can be considered a surrogate for sperm binding to the endocervical mucus and the hyaluronan-rich cumulus oopherous complex) and spermatozoal viability, was established in the 1990s (Vandevoort et al 1997;Cayli et al 2003). This, and related work, suggest that spermatozoa capable of binding to hyaluronic acid have completed their maturation processes, most specifically plasma membrane remodelling and full chromatin condensation, and subsequently have an increased fertilizing capacity (Cayli et al, 2003;Huszar et al, 2003;Mokanszki et al, 2014). Different studies have suggested that hyaluronic-acid-binding improves embryo quality and development after ICSI, although all these studies were relatively small (Nasr-Esfahani et al, 2008;Parmegiani et al, 2010a;Parmegiani et al 2010b;Mokanszki et al, 2014;Beck-Fruchter et al, 2015).…”
Section: Changes In Sperm Hyaluronic-acid-binding and Hyperactive Motmentioning
confidence: 99%
“…The largest study to date reported a significant drop in pregnancy loss but unfortunately failed to report birth outcomes (Worrilow et al, 2013). A more recent report showed a significant improvement in live births although the lack of available raw data led to the study's exclusion from a later meta-analysis that recommended the need for better clinical trials with full data reporting (Mokanszki et al, 2014;Beck-Fruchter et al, 2015).…”
Section: Changes In Sperm Hyaluronic-acid-binding and Hyperactive Motmentioning
confidence: 99%
See 1 more Smart Citation